Percepções e concepções sobre o atendimento ao idoso: um estudo com os profissionais de enfermagem que atuam nas Unidades de Saúde da Família – USFs - Fonseca, Laura Moreira de Sousa (2012)
Introduction: Population aging is a process that happens quickly, becoming important worldwide phenomenon. The aging population has brought changes in the morbidity and mortality of the adult population. Thus, it is essential that health professionals be prepared to deal with this new profile of the population. Objectives: To analyze the perceptions and conceptions that nursing professionals have about senior care, identify the difficulties faced by them in senior care, and the types of knowledge or professional experience / personal that professionals reported to be essential in senior care . Method: This is a qualitative descriptive study that was conducted with nursing professionals (nurses, technical and nursing assistants) who work in the city of USF's Coromandel - MG. We used semi-structured interviews that were transcribed and categorized by subject. Results: We noted that most participants see the elderly as a 'be able', which 'has so much knowledge gained over the years', but on the other hand 'people needing care and attention' and who have some kind of dependence, a consequence the very process of aging. Understand that the elderly need, therefore, special care by the nurses and greater attention and care of family members. The main difficulties reported by these professionals were: a) lack of knowledge of the peculiarities in senior care, b) the overhead of service that is imposed on these professionals, c) the neglect of family, d) the difficulty of adherence to treatment by the elderly. Conclusion: The elderly have their peculiarities, and nursing staff should make use of their knowledge to guide them and their families so that there is a better adherence to treatment but also in awareness of rights and obligations as a user of the health system. It is essential that users are able to establish partnership between them and health professionals, thus not only the practical results would be more promising to broaden the opportunities to prevent damage, which contribute to active aging with quality of life, this assumption, the Promotion of Health Although they have reported their difficulties in caring for the elderly, the professionals in question claimed could overcome these difficulties through experience, appealing to the type of bond that seems to establish between them and the elderly, many times supplanted the technical and structural deficiencies, and lack of a better structure for the care of this population group, thus making feasible because the service is based on the human aspect to the detriment of conditions and structure of professional work.